A prospective diagnostic study on povidone–iodine retention in lesions suspected to be squamous cell carcinoma or keratoacanthoma. (15th August 2018) - Rizk, Mariam; Alian, Mehrnoosh; Tschandl, Philipp; Gorgi, Madieh; Hishon, Matthew; Clark, Simon; Kittler, Harald; Rosendahl, Clifford
Abstract: Background and objectives: While dermatoscopy improves diagnostic accuracy for raised nonpigmented lesions, those with white surface keratin can be problematical. We investigated whether retention of povidone–iodine by surface keratin provides a clue to benignity. Methods: We performed a retrospective pilot study ( n = 57) followed by a prospective study ( n = 117) on raised nonpigmented lesions with white surface keratin. An initial dermatoscopic image was taken of each lesion, povidone–iodine was applied and another image taken. Following lavage with 70% ethanol, a third image was acquired. The percentage surface area of residual povidone–iodine staining after lavage was recorded, and the results analysed. Results: The optimal cut‐off point of residual staining was 80%, where values of ≤80% pointed to malignancy. At this cut‐off, the OR for lesions with values ≤80% to be truly malignant in the retrospective set was 4.03 (95% CI: 2.1–7.6) and the AUC was 0.7 (95% CI: 0.62–0.78). For the prospective set, the corresponding OR was 2.3 (95% CI: 1.4–3.7) and the AUC was 0.62 (95% CI: 0.55–0.68). Conclusions: This study presents evidence that povidone–iodine retention may have a degree of efficacy in distinguishing benign from malignant keratotic lesions. Further study is warranted.